Structural Barriers for Development of Nepal Analyzing Political, Economic, and Institutional Obstacles - Poudel, Komal (Aadim Journal of Multidisciplinary Research, 2025)
Nepal has been facing developmental impediment for a long. Nepal is a least developed country designed by United Nation in 1971 and has the same developmental position since that time about 54 years. Nepal has huge potentialities for achieve of its national interests and augment of its position. Nevertheless, the economic growth is not improving, security is in vulnerable, and development is in stagnation. Consequently, Nepal is bearing high international trade deficit and debt of annual interests. Being a least developed country, Nepal has been challenging with several non-traditional security threats. The objective of the article is to unveil the reasons of developmental impediments of Nepal for a long critically. The article has attempted to elucidate political structural, institutional structural, economic, procedural, and policy of developmental obstacles. Furthermore, potentialities for augment its developmental position and the consequences of development impediment have also been disclosed. Philosophy of constructivism and analytical interpretive approaches are applied. Qualitative research design is adopted, mainly phenomenology and history qualitative methodology is employed. Development and peace theory is considered. Secondary and few primary qualitative data have been collected.